Highly Active Nonpromoted Hydrotreating Catalysts through the Controlled Growth of a Supported Hexagonal WS2 Phase - Alphazan, Thibault; Bonduelle-Skrzypczak, Audrey; Legens, Christèle; Gay, Anne-Sophie; Boudene, Zoubeyr; Girleanu, Maria; Ersen, Ovidiu; Copéret, Christophe; Raybaud, Pascal (ACS catalysis, 2014)
Highly active nonpromoted W-based hydrotreating catalysts are prepared through a molecular approach with a control of each step. This approach yields WS2 crystallites exhibiting hexagonal 2D morphology, which have been characterized by combining XPS and HR HAADF-STEM techniques and ab initio molecular modeling. The first step is the impregnation of a well-defined precursor, [W(OEt)5]2, grafted onto partially dehydroxylated amorphous silica–alumina (ASA) and characterized at the molecular level by spectroscopic techniques (NMR and IR). The use of increasing amounts of W precursor reveals the formation of (i) a layer of tungsten surface species grafted on the surface and (ii) layers of more mobile adsorbed species loosely bonded to the surface. Sulfidation of these materials provides WS2 supported on ASA, which shows unprecedented lower sulfidation temperatures down to ambient temperature and improved activity by comparison with conventional references (polyoxometalate route). In addition, these improved activities are explained not only by a better level of sulfidation but also by the 2D hexagonal-like morphology of WS2 crystallites (revealed by HR HAADF-STEM), in contrast to a truncated triangle-like morphology for conventional samples. This molecular approach thus opens new avenues to understand and improve the performances of hydrotreating catalysts.